Ultrasound-guided collagen injections for treatment of plantar fasciopathy in runners: A pilot study and case series - Corrado, B.; Bonini, I.; Tarantino, D.; Sirico, F. (Journal of Human Sport & Exercise, 2020)
Background: Plantar fasciopathy is a frequent source of foot pain in athletes, and it is caused by the degeneration of the proximal insertion of the plantar fascia, usually triggered by repetitive microtrauma. Type I porcine collagen was shown to enhance tendon repair in vitro, and collagen injections are currently used to treat different tendinopathies. The aim of this study is to verify the effectiveness of collagen injections on pain and function in runners with plantar fasciopathy. Methods: Runners, who have been suffering from plantar fasciopathy for at least 6 months, were treated with a series of 4 ultrasound-guided type I porcine collagen injections, at weekly intervals. The Visual Analogue Scale, American Orthopedic Foot and Ankle Society-Ankle Hindfoot score and pressure algometry were used to verify the effects of collagen injections at 1-month and 3-month follow-up. Results: Compared to baseline, minor (p = .05) and major (p = .001) improvements on pain and function were registered at 1-month and 3-month follow-up, respectively. Conclusion: This is the first study that evaluates the effectiveness of collagen injections in the treatment of plantar fasciopathy in runners. Despite the limitations of this study, the positive findings could represent the starting point for further clinical trials.